Robotic scanning free-space measurement system for electromagnetic performance evaluation of curved radar absorbing structures. (27th July 2022) - Din, Salah ud; Hyun, Jong-Min; Son, Dae-Sung; Lee, Jung-Ryul
Radar absorbing structures are manufactured for stealth missions and total quality inspection applies to evaluate their performances before assembly to stealth weapon systems. This study adopted a six-axis robot arm to move a target specimen in a scanning free-space measurement system for electromagnetic performance evaluation. The six-axis robot arm completely enables the system to maintain the specimen at the focal point of the antenna and solves the issue of curvature effect on the return loss results of the curved specimens, faced in the two- and three-axis scanning free-space measurement systems. The six-axis robotic scanning free-space measurement system uses a RobotStudio to extract the position and orientation of each target point on the specimen to be evaluated and uses a robotic scanning algorithm to transform all the points into a scan path. The system was verified by variable and constant curvature radar absorbing structure specimens with frequency selective surfaces. Return losses ( S 11 s) of the nonsymmetrical cambered airfoil specimen and S-shaped double curvature specimen that could not be accurately evaluated with a three-axis stage-based scanning free-space measurement system were measured by the six-axis robotic scanning free-space measurement system. All the specimen results adhere to the theoretical parameters of the specimen. The transition region results of the S-shaped specimen were studied using effective radius of curvature. Finally, the inspected results of the S-shaped specimen were curvature compensated to check the effect of negative and positive curvature on the specimen resonance frequency performance.